Relationship between student engagement and academic achievement in college english education for non-english majors in China - Liu, Mengjie; Noordin, Nooreen; Ismail, Lilliati; Abdrahim, Nur Aira (Society for Research and Knowledge Management, 2023)
To address the tangible problem of English underperformance and recognize a theoretical void in student engagement theory within the realm of college-level English education for non-English majors in China, this research investigated the correlation between student engagement and English achievement in this unique setting. Additionally, it analyzed to what degree the trio of student engagement dimensions (specifically, emotional engagement, cognitive engagement, and behavioral engagement) elucidate or forecast students' accomplishments in English. The correlation study design was adopted with 400 non-English major undergraduates in 6 public universities and colleges in Hebei Province, China. Students’ CET-4 scores served as indicators to assess academic achievement, which was collected in the Demographic Information Form. The Student Engagement Scale collected data on three dimensions of student engagement. Through comprehensive statistical analyses, the outcomes demonstrated substantial and positive correlations between (the three dimensions of) student engagement and English achievement in the domain of college English education for non-English majors in China. Notably, these dimensions collectively elucidate 65.3 of the variation in English achievement, with emotional engagement emerging as the primary predictor, succeeded by behavioral engagement and cognitive engagement. These findings not only suggest a path for tackling the practical issue but also expand the application boundaries of student engagement theory. As subsequent research delves into the intricacies of student engagement, this study establishes a foundation for delving deeper into the mechanisms that propel English achievement within this distinctive educational landscape.